Properties of microdischarge plasma in the vortex air flow - Chernyak, V.Y.; Kolomiiets, O.V.; Iukhymenko, V.V.; Tsymbaliuk, O.N.; Khomiak, V.O.; Chernysh, D.O. (Вопросы атомной науки и техники, 2018)
In this paper the microdischarge in a vortex gas flow was studied. The important values in it are components of the flow velocity transverse to the current channel. This provides both enhanced heat-mass transfer of the plasma to the surrounding environment and the gliding of the discharge along the surface of the electrodes. The first contributes to the nonisothermal nature of the plasma, and the second reduces the removal of the material of the electrodes into the plasma. The temperatures of excited vibrational levels and excited rotational levels of molecules ware determined from an emission spectra of the microdischarge by using a Specair code. The electric field in the microdischarge plasma was estimated by the dependence of the voltage drop on the discharge at different interelectrode distances. The average electron energy and the electron energy distribution function were determined using code Bolsig +.